Interferon inducibility of STAT 1 activation and its prognostic significance in melanoma patients - Boudný, V; Kocák, I; Lauerová, L; Kovarík, J (Folia biologica, 2003)
STAT 1, a member of latent cytoplasmic proteins, plays a pivotal role in mediating biological effects of interferons. Its transducing, DNA binding and transcriptional activity require phosphorylation at both Tyr 701 (Y 701) and Ser 727 (S 727) residues. Deficient phosphorylation or constitutive activation of the STAT 1 protein were observed in some human malignancies. Using immunoprecipitation and Western blots performed with lysates made of melanoma cells derived from patients with clinical stage II/III and employing specific anti-STAT 1 PS 727/PY 701 immunoprobes, we show that STAT 1 activation response induced by IFN-alpha/-gamma is significantly impaired. On average, three quarters of patients were lacking phosphorylation at S 727. STAT 1 PY 701 was not inducible by IFN-alpha in 63% and by IFN-gamma in 34% of samples. However, these STAT 1 activation defects showed no correlation with the disease outcome and immunotherapy response as indicated by progression-free survival profiles in patients treated with IFN-alpha2b.
Keywords: fosforylace; STAT1 Transcription Factor; interferony; melanom; prognóza; DNA vazebné proteiny; lidé; transkripční faktor STAT1; Phosphotransferases; DNA-Binding Proteins; Interferons; Melanoma; Trans-Activators; fosfotransferasy; trans-aktivátory; Phosphorylation; Humans; Prognosis